2007
DOI: 10.1002/cyto.b.20370
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric lymphocyte subset enumeration: 10 years of external quality assessment in the Benelux countries

Abstract: A biannual external quality assessment (EQA) scheme for flow cytometric lymphocyte immunophenotyping is operational in the Benelux countries since 1996. We studied the effects of the methods used on assay outcome, and whether or not this EQA exercise was effective in reducing between-laboratory variation. Eighty test samples were distributed in 20 biannual send-outs. Per send-out, 50-71 participants were requested to enumerate CD3 + , CD4 + , and CD8 + T cells, B cells, and NK cells, and to provide methodologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…Data collected in the present study indicate that CVs of the improved flow cytometry procedure fall well within the range of CV values observed in large international quality assay exercises for the enumeration of other rare circulating cell populations such as CD34 + hematopoietic progenitors or some lymphocyte subsets (21,22). Although CEC/CEP enumeration in fresh samples has the advantage of allowing an absolute cell count (in frozen samples, after mononuclear cell purification, the absolute cell count is calculated based on a complete blood cell count obtained at the same time of blood collection; see ref.…”
Section: Discussionsupporting
confidence: 75%
“…Data collected in the present study indicate that CVs of the improved flow cytometry procedure fall well within the range of CV values observed in large international quality assay exercises for the enumeration of other rare circulating cell populations such as CD34 + hematopoietic progenitors or some lymphocyte subsets (21,22). Although CEC/CEP enumeration in fresh samples has the advantage of allowing an absolute cell count (in frozen samples, after mononuclear cell purification, the absolute cell count is calculated based on a complete blood cell count obtained at the same time of blood collection; see ref.…”
Section: Discussionsupporting
confidence: 75%
“…In the case of small populations, which are given similar weight in standardized lymphocyte fractions, small variations in staining intensity can lead to large VARIABILITY AND CLUSTERING OF LYMPHOCYTE SUBSETS relative changes. Others have also found that variability was proportionally greater for measurements of numerically smaller subsets of lymphocytes (5,6,10,12). In the case of absolute cell counts, additional sources of variation including analytical (e.g., the complete blood count (13), and the use of a dual platform method, as discussed above) and biological [e.g., diurnal shifts (14)], contribute to increased inter-and intraindividual variability.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of lymphocyte subset enumeration, the results indicated no significant difference between "lyse no wash" and a few observations using "no lyse no wash" methods from those obtained using "lyse and wash" methods (38). Some consider, no lyse-no wash methods better suited for absolute counting, for example enumeration of CD341 cells or CD41 T-cells (39,40).…”
Section: Surface and Intracellular Staining: Lysis And Permeabilizatimentioning
confidence: 97%
“…Simple serial dilution antibody titrations against both positive and negative cellular targets are invaluable for antibody concentration optimization. It is preferable to perform antibody titrations against multiple sample sources that cover the expected range of population percentages and antigen expression as will be observed in the sample population (38). Use of cell lines is only acceptable for the evaluation of antibodies not expressed in healthy samples and to evaluate antibody performance at extreme limits of expected ranges.…”
Section: Antibody and Fluorochrome Conjugate Optimizationmentioning
confidence: 99%